Antiprotozoal 6-substituted-5,6-dihydro-alpha-pyrones from Raimondia cf. monoica. (2003)
ABSTRACT: Dichloromethane extracts of both the roots and the leaves of Raimondia cf. monoica showed in vitro antiplasmodial and leishmanicidal activities against Plasmodium falciparum and Leishmania panamensis, respectively. Three 6-substituted 5,6-dihydro-2H-pyran-2-ones were isolated. (1) and (2) were identified as (6S)-(5′-oxohepten-1′E,3′E-dienyl)-5,6-dihydro-2H-pyran-2-one (1) and (6R)-(5′-oxohepten-1′Z,3′E-dienyl)-5,6-dihydro-2H-pyran-2-one (2), respectively. (-)-Argentilactone (3) was also isolated. The structure of the new compound (1) was determined by spectroscopic methods; additional spectroscopic data for (2) are reported for the first time